ASSESSING EFFECTS OF CUCURBITURILS ON MONOCYTES AND NK-CELLS IN HEALTHY VOLUNTEERS - A. A. Aktanova; E. A. Pashkina; V. A. Kozlov (Медицинская иммунология, 2021)
Nanotechnology in immunology is a prospectively developing area in fundamental and practical medicine. Cucurbiturils are macrocyclic cavitands with a definite amount of glycoluril fragments (n) that determine the size of the cavity of these compounds. Nowadays, there are six synthesized homologues: 5, 6, 7, 8, 10 and 14. They differ from each other in the portal size and the size of the cavities. They are characterized by special physicochemical and biological properties, such as biocompatibility, stability, high ability to encapsulate chemical compounds. It is known that cucurbiturils encapsulate molecules by forming guest-host complexes, which allow the substance to be released from the complex and increase the solubility of the compounds. These advantages allow using cucurbiturils as drug delivery systems. Immunomodulatory activity of cucurbiturils depends on its specific nanoscale characteristics: functional groups, shape, size, surface, solubility in various media. Each nanoparticle depending on these properties has different effects on cells. The effects of cucurbiturils can be different even for one subpopulation of cells, depending on the homologue or dosage. The interaction of innate immune cells with cucurbiturils are not yet sufficiently characterized.The aim of this study was to assess the effects of cucurbit[n]urils (n = 6, n = 7, n = 8) on innate immune cells – monocytes, NK-cells, NKT-cells.The immunological recearch included the isolation of peripheral blood mononuclear cells from healthy donors (n = 8) on the density gradient of ficoll-urografin and flow cytometry with the determination of the amount of immunocompetent cells according to the classic markers of differentiation of these cells – CD3- CD16+CD56+ for NK-cells, CD3+CD16+CD56+ for NKT-cells and CD3- CD14+ for monocytes. Monocyte activation was determined by the expression of surface HLA-DR.The cells were cultured for 72 hours with the addition of cucurbiturils CB[6], CB[7] at concentrations of 0.1 mM, 0.3 mM, 0.5 mM and CB[8] at concentration of 0.01 mM, due to its poor solubility.There were a significant decrease in the quantity of NK-cells (p < 0.01 for the test concentrations of CB[7]), an increase in the quantity of NKT-cells (p < 0.04 and p < 0.02 respectively for the concentrations of CB[6] and CB[7]). There was a tendency to increase the expression of HLA-DR on monocytes (p = 0.06 for CB[6]).Considering a variative effects of cucurbiturils, in the future it is possible to consider a possibility of using cucurbiturils as an immunomodulators, antitumor agents, in autoimmune diseases.